The export of the guava from Mexico to the world market - López-Valle, Isela Janeth; Oliva-López, Eduardo; León-Puertos, Cuauhtémoc (Revista Mexicana de Ciencias Agrícolas, 2026)
Guava is a fruit widely accepted worldwide and in 2023, Mexico consolidated its position as the second-largest global exporter, with a value of 577 934.18 USD, confirming its high international competitiveness. The research aimed to analyze the competitiveness of Mexican guava in international trade, identifying its position and formulating alternatives that strengthen its insertion into international trade. The research was conducted by calculating growth rates and trade competitiveness indices for the period 2000-2023, using production and foreign trade data. The results showed that the indicators were positive: the trade balance remained at 1, which confirms that Mexico is an exporter with competitive advantages; the tradability indicator was 0.34, evidencing an excess of exportable supply; the trade dependence coefficient was 0, which reflects food self-sufficiency; and the degree of export openness reached 0.035, pointing out the existence of exportable surpluses. Overall, these results indicate that guava production in Mexico is expanding, with a marked export specialization and a solid competitive position in the international market.t.
Keywords: exports; guava; imports; production; trade balance